Attention Skills in Children With Neurofibromatosis Type 1. (January 2013) - Isenberg, Jill C.; Templer, Alexandra; Gao, Feng; Titus, Jeffrey B.; Gutmann, David H.
Children with neurofibromatosis type 1 are at increased risk for the development of attention problems relative to their unaffected peers. Previous studies have reported deficits in sustained auditory attention, but other aspects of attention, including sustained visual attention, divided attention, response inhibition, and selective attention, have not been consistently documented. In the present study, we specifically investigated attention skills in children with neurofibromatosis type 1 using measures of visual and sustained auditory attention, divided attention, selective attention, and response inhibition. Consistent with previous reports, we confirmed the presence of deficits in sustained visual and auditory attention in children with neurofibromatosis type 1 but also identified deficits in divided attention and response inhibition. Based on the high frequency and wide spectrum of attention system impairments in this at-risk population, we advocate screening children with neurofibromatosis type 1 for attention problems and providing appropriate interventions that address all aspects of their executive functioning.